The Role of School Asset Management in Enhancing the Quality of Early Childhood Education: A Case Study of TKN Pembina Bugul Kidul and TK Al Kautsar, Pasuruan City - Rini Kurniati; Taufiq Harris; M. Furqon Wahyudi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Early Childhood Education (ECE) serves as a fundamental foundation for the development of children's character, cognitive abilities, socio-emotional skills, and learning readiness. To provide high-quality ECE services, schools are required not only to excel in the learning process but also to manage their assets effectively and sustainably. School asset management constitutes an essential component of educational quality management, as it supports all educational services and learning activities. This study aims to analyze school asset management planning, identify the factors influencing its implementation, and describe its impact on improving school quality at TKN Pembina Bugul Kidul and TK Al-Kautsar in Pasuruan City. The research employed a qualitative approach using a case study method. Data were collected through in-depth interviews with school principals and teachers, direct observations of school asset utilization, and document analysis of asset planning and inventory records. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and methodological triangulation. The findings indicate that asset management planning in both schools has been developed based on instructional needs and student services and aligned with the School Work Plan (RKS) and the School Activity and Budget Plan (RKAS). Nevertheless, several assets have not yet been utilized optimally. Factors such as principal leadership, budget availability, human resource competencies, inventory management systems, and community involvement significantly influence the effectiveness of school asset management. Well-managed school assets have been shown to positively contribute to improved learning quality, a more conducive school environment, efficient resource utilization, and increased public trust in educational institutions.